Serological study of Human Parvovirus (B19) detected among Patients with Thalassemia - Ahmed Waleed Dheyab Alnassar; Mohammed Jasim Mohammed Shallal (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Parvovirus B19 is an icosahedral, single-strand DNA, non-enveloped virus. Its DNA genome has 5596 bases and is from the Parvoviridae family. Beta thalassemia, a hereditary illness, causes ruptured red blood cells and acute anemia due to aberrant haemoglobin synthesis.Aim: Detect parvovirus (B19) in β-thalassemia major and study its association with demographic factors like sex, age, place of residence, etc. in specific patient groups.Methods: From August 2022 to the end of February 2023. This study included the collection of serum samples for the detection of human parvovirus antigen in 60 patients with β-thalassemia major. The control group consisted of 30 individuals of different ages who did not have thalassemia-beta. All these serum samples are detected for parvovirus antigen by the ELISA method.Results: The results of this study showed that the rate of detection of the presence of human parvovirus B19 in the group of patients with β-thalassemia major was not affected by most of the demographic factors. As there were no statistically significant differences between the study groups in terms of gender, age, in addition to COVID-19 infection, and vaccination against COVID-19. However, the rate of β-thalassemia major was significantly higher in rural areas than in urban areas (p = 0.040).